MINA SAMUDERA VILLAGE UNIT COOPERATIVE DEVELOPMENT STRATEGY IN CITUIS, PAKUHAJI, TANGERANG DISTRICT - Anwar, Muhammad Khoirul; Ediyanto; Telussa, Riena F (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2024)
Koperasi Unit Desa (KUD) Mina Samudera is one of the most rapidly growing cooperatives in Tangerang Regency, with a total membership of 9,877 people. This study was conducted in May 2017 at KUD Mina Samudera, Pakuhaji District, Tangerang Regency, using descriptive statistical analysis, motivation theory, and SWOT analysis. KUD Mina Samudera operates four main business units: the Swamitra Mina Savings and Loan Unit (USP), Pesisir Store, Grameen Pesisir , and the Fishermen’s Fuel Station (SPDN). These business units have consistently increased their annual profits and provided significant benefits to fishermen, including financial support, logistics, fuel, and additional business opportunities for their wives. A growth and development strategy serves as an alternative approach for the cooperative by optimizing its financial strength, management, and existing business units. However, challenges remain, including limited access to information and location, low community participation, and the need for more competent human resources. To address these issues, improving cooperative accessibility, increasing member participation, and fostering collaboration with the government are essential to ensuring the sustainability and growth of the cooperative.